CERMINAN TRANSPARANSI DAN AKUNTABILITAS PUBLIK MELALUI WEBSITE PEMERINTAH DAERAH - Sylvia Sylvia (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
Financial reporting is one of the important information to describe the financial condition of the area. Transparent and accountable local government would make adequate voluntary disclosure to the public about government performance. This research is limiting itself to compulsory taxes and charges, as well as investors and creditors. The reason is that the general public as taxpayers would like to know the local tax revenue realization that they have to pay and follow-up of local government in managing the tax proceeds. Investors are parties to invest their funds in local government, and the current government is encouraged to attract investors to work together with local government to local governments in developing regions are not only dependent on central government funding